Designing of internal model control proportional, integral, and derivative controller with second‐order filtering for lag‐ and delay‐dominating processes based on suitable dead time approximation. Issue 6 (7th November 2019) - Nath, Ujjwal Manikya; Dey, Chanchal; Mudi, Rajani K.
Abstract: In practice, majority of the industrial chemical processes contain considerable dead time and significant process lag. Depending on the value of dead time to time constant ratio, industrial processes can be classified as lag dominating and delay dominating in nature. Here, an attempt has been made to find out an improved dead time estimation technique from the available methodologies like Taylor series and Pade's approximation relations so that a more accurate process model can be obtained and, consequently, an enhanced model‐based internal model control based proportional, integral, and derivative (IMC‐PID) controller may be designed. In addition, to ensure an improved closed loop performance, a second‐order filter is incorporated in IMC‐PID structure where damping term of the filter is calculated from dead time to time constant ratio of the concerned process. Efficacy of the proposed scheme is verified through simulation study on first‐order plus dead time, second‐order plus dead time, higher order, and nonminimum phase processes in comparison with recently reported model‐based PID settings. In addition to simulation study, a real‐time experimental verification is also made on a level control loop under transient and steady state operating phases.